High-Dose Nitroglycerin Bolus and Non-Invasive Ventilation Prevent Intubation or ICU Admission on Hypertensive Emergency and Acute Pulmonary Edema: Sympathetic Crashing Acute Pulmonary Edema (SCAPE) Treatment on STEMI Patient: A Case Report - Mahendra Eko Saputra; Achmad Lefi; Makhyan Jibril Al Farabi; Pandit Bagus Tri Saputra; Ariikah Dyah Lamara (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlight: 1. SCAPE could lead to respiratory failure when not treated promptly. 2. High-dose NTG and NIV support can be used as an alternative treatment to overcome hypertensive emergency and pulmonary edema, thus preventing the need for endotracheal intubation and ICU admission. - Background: A marked elevation in blood pressure that causes acute heart failure and fluid accumulation in the lungs is known as sympathetic crashing acute pulmonary edema (SCAPE). Here, we present a SCAPE patient with severe respiratory failure who was successfully treated with high-dose nitroglycerin (NTG) bolus and non-invasive ventilation (NIV). Case summary: A 48-year-old male was referred to our center with typical chest pain and dyspnea. Physical and additional examination found hypertensive emergency (196/66 mmHg), acute pulmonary edema, and acute heart failure, accompanied by anterior STEMI and severe respiratory failure (P/F ratio of 72) in need of intubation. He was given 2 mg intravenous NTG bolus twice supported with NIV, diuretics followed by the primary percutaneous coronary intervention (PCI) stenting in mid left anterior descending (LAD). The patient recovered from acute pulmonary edema, and the P/F ratio improved from 72 to 321 without intubation. Discussion: SCAPE could lead to respiratory failure requiring intubation and intensive care unit (ICU) admission when not treated promptly. The administration of large doses of NTG and NIV was safe and resulted in a speedy improvement in symptoms. Conclusion: SCAPE can be resolved without invasive procedures, using high-dose NTG and NIV support to overcome hypertensive emergency and pulmonary edema.